Comparative Analysis of Aircraft Modification Processes: EASA, FAA, and DGCA Indonesia - Ramadhanti, Nurfrida Nashira; Pasaribu, Hisar Manongam (Warta Penelitian Perhubungan, 2023)
This study conducts a comparative analysis of aircraft modification certification processes within the aviation regulatory frameworks of the Federal Aviation Administration (FAA), the European Union Aviation Safety Agency (EASA), and the Directorate General of Civil Aviation (DGCA) in Indonesia. Using the TCAS 7.1 Software Updates modification on the A320-200 as a case study, the research explores Design Organization Approval (DOA) or Organization Designation Authorization (ODA) procedures. The findings reveal variations in Design Organization structures and certification processes, offering valuable insights for Indonesia's emerging aviation market. By adapting best practices from the FAA and EASA, the study aims to contribute to the enhancement of Indonesia's regulatory system, benefiting policymakers, regulators, and industry stakeholders.